BULL’S EYE: IS THIS PHENOMENON GIVEN ENOUGH ATTENTION - Gjeorgjieva Janev, Olivera; Mediha Lushi Selimi; Pecanova, Blagica; Pachoska, Vesna; Karanfilovski, Vlatko; Pandilov, Stefan; Damjanovska Krstikj, Ljubinka (Macedonian Association of Anatomists and Morphologists, 2024)
Chloroquine maculopathy is not such a rare complication of long-term use of chloroquine preparations in the treatment of rheumatological diseases. Its early detection is of exceptional importance for timely discontinuation of the drug in order to preventirreversible vision damage.The aim of this Article is to present a case of a 62-year-old patient with bull's eye maculopathy as a result of long-term use of chloroquine due to systemic lupus erythematosus. The patient appeared with blurring and distortion of the pericentral vision. She was ophthalmologically evaluated with fundoscopic examination, autofluorescence, perimetry, optical coherent tomography which together with her medical history established a diagnosis of chloroquine maculopathy. Chloroquine therapy was discontinued and the patient is regularly monitored by a Rheumatologist and an Ophthalmologist, with no disease progression so far.
Keywords: Bull’s eye; retinopathy; hydroxychloroquine